SKILLS AS A DETERMINING FACTOR OF WAGE LEVELS IN THE CONSTRUCTION SECTOR - Mawadda, Nur; Arif Musthofa, M.; Nurjali; Wandi (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
This study aims to analyze the effect of skills on the wage level of construction workers in Rano Village. This study uses a quantitative approach with a population of 75 construction workers. The sample determination was carried out using the Purposive Sampling technique, while the number of samples was calculated using the Slovin formula, so that 63 respondents were obtained. Data collection was analyzed through a simple linear regression technique using SPSS version 25 software to ensure the validity of the results. The results of the study indicate that skills have a significant effect on the wage level of construction workers. This is indicated by the coefficient of determination (R Square) of 0.595 or 59.5%, which indicates that skills explain 59.5% of the variation in wage levels. The remaining 40.5% is explained by other factors outside the scope of this study, such as work experience, education level, and labor market conditions. This study provides important insights into the importance of improving skills as an effort to improve the welfare of construction workers. These findings are expected to be a reference for policy makers and related parties in designing more effective training and skills development programs in the region.